Analisis Indeks Kekeringan Menggunakan Teori Run Pada Daerah Aliran Sungai Palambayan - Wiliya Wiliya; Manyuk Fauzi; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Drought is the decrease in the amount of rainfall from its normal condition and depends on how long it lasts. This study aims to determine the characteristics of drought that occurs in the longest duration of drought and the largest number of drought in the location of rain stations spread in Palambayan basin. Then can be used as early warning of drought disaster and help for the interest of planning design at Palambayan watershed. The method used to analyze drought is Run Theory method. The location of the study was in the Palambayan Basin of West Sumatra Province. The data used are monthly rainfall for 10 years (2007-2016) from 2 rain stations located in the Palambayan River Basin and 1 Rain Station located outside the Palambayan River Basin. The results showed that the largest cumulative drought occurred in 2008 of 283.49 mm at Muaro Tantang rain station. For the longest duration of drought is 9 months in 2009. Based on the result of drought distribution map using Geographic Informaton System (GIS), the worst drought station is Gumarang Station.Keywords: Drought Analysis, Run Theory, Drought Index